2004
DOI: 10.1115/1.1798951
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Combined Lorentz-Doppler Broadening in High-Temperature Radiative Heat Transfer Applications

Abstract: The importance of combined Lorentz-Doppler (or Voigt) broadening of spectral lines in high-temperature radiative heat transfer applications is investigated. Employing narrow-band transmissivities as the criterion, the critical total pressure below which, and the critical temperature above which Doppler broadening has a significant effect on the absorption coefficient is established for gaseous H2O and CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The Lorentz profile was used for the shape of spectral lines based on the line characteristics obtained from the spectral database of HITEMP2010. For the pressures equal or higher than 1 bar and temperatures less than 2500K, the Doppler broadening is negligible and therefore Lorentz profile sufficiently describe the shape of the absorption lines [34]. A minimum limit of 10 -9 cm -1 has been used for the line wings to be included (i.e.…”
Section: Line By Line Absorption Spectra Of Combustion Gasesmentioning
confidence: 99%
“…The Lorentz profile was used for the shape of spectral lines based on the line characteristics obtained from the spectral database of HITEMP2010. For the pressures equal or higher than 1 bar and temperatures less than 2500K, the Doppler broadening is negligible and therefore Lorentz profile sufficiently describe the shape of the absorption lines [34]. A minimum limit of 10 -9 cm -1 has been used for the line wings to be included (i.e.…”
Section: Line By Line Absorption Spectra Of Combustion Gasesmentioning
confidence: 99%
“…Although the Voigt profile might be the best option to describe the spectral line broadening at high pressures and elevated temperatures, the studies of Ref. [15] showed that it is still accurate to apply the Lorentz profile for the physical conditions studied in this paper. Linear interpolations were used for in-between values of temperature and mole fraction.…”
Section: Methodsmentioning
confidence: 90%
“…The dependences of κ η,i , N and C η,i on η, p, T , and Y i were left explicit in the above equation, from which it can be seen that the wavenumber dependence of the absorption spectrum is inherited solely from the absorption cross-section. The spectral absorption coefficient was obtained based on Lorentz's line broadening [34] using the high-resolution spectroscopic database HITEMP2010 [35]. More details of the methodology can be found in [13,21,23] 5 For the line-by-line integration method (applied both for constructing the emmitance charts in Section 3 and as a reference for the radiative transfer calculations reported in Section 5) the κ η,i spectra for H 2 O and CO 2 is obtained for 150000 wavenumber values between η = 100 and η = 10000 cm −1 .…”
Section: Generating Absorption Spectral Datamentioning
confidence: 99%